Genome-wide association studies for identifying genetic architecture of SGRQ in smoking population - Hao Xinying; Zhu Jun (浙江大学学报. 农业与生命科学版)
The dualism of genetic predisposition and gender influences has long been a hot topic in the development of chronic obstructive pulmonary disease (COPD), and smoking is considered a primary risk factor for this lung disease. This paper aimed to detect susceptibility genes for COPD with the data downloaded from dbGaP. A linear mixed model was employed to conduct association-mapping QTSs (quantitative trait single-nucleotide polymorphisms) because of its effectiveness in unbiased estimation of random effects with unbalanced data and in controlling population stratification. The primary focus of the study is to identify genetic risk factors that determine susceptibility for COPD and COPD-related phenotypes with the goal of providing insight into clinically relevant COPD subtypes. By comparing the conditional model excluding the cofactor smoking with the full model, we can detect related QTSs, which will reveal the gene expression on COPD caused or suppressed by smoking. As a result, there are significant genes with high heritability: TNS1 and DGKH were not caused by smoking, MACROD2 and CNIH3 were due to smoking, and LINC00426, METTL4 and GSDMC were suppressed by smoking.